2011
DOI: 10.1016/j.jcta.2011.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Divisible designs and semi-regular relative difference sets from additive Hadamard cocycles

Abstract: Additive Hadamard cocycles are a natural generalization of presemifields. In this paper, we study divisible designs and semiregular relative difference sets obtained from additive Hadamard cocycles. We show that the designs obtained from additive Hadamard cocycles are flag transitive. We introduce a new product construction of Hadamard cocycles. We also study additive Hadamard cocycles whose divisible designs admit a polarity in which all points are absolute. Our main results include generalizations of a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Proposition 2.2 is a direct consequence of Lemma 4.5 in [10]. We will call a nondegenerate quadratic form over F q a quadratic bent function over F q .…”
Section: Non-degenerate If and Only If Q Is A Bent Functionmentioning
confidence: 96%
See 2 more Smart Citations
“…Proposition 2.2 is a direct consequence of Lemma 4.5 in [10]. We will call a nondegenerate quadratic form over F q a quadratic bent function over F q .…”
Section: Non-degenerate If and Only If Q Is A Bent Functionmentioning
confidence: 96%
“…We define H 1 (α) = {x ∈ F q | tr q/q (αx) = 0 and x = 0} and 10 and C 20 be the subgroups of index q + 1 and q 2 n + 1, respectively, in F * q 2 m+n . Then C 10 , C 20 = S q 2 m+n and S q 2 m+n is the union of (q + 1)/2 cosets of C 10 and N q 2 m+n is the union of (q 2 n + 1)/2 cosets of C 20 .…”
Section: Non-degenerate If and Only If Q Is A Bent Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng in [25] constructed a family of Paley type group schemes in extra-special p-groups of order p 3 and of exponent p for p > 3, and his construction was generalized by Chen and Polhill in [17] using the flag group of finite fields (see [12]). In [36], Muzychuk obtained a large number of Paley type group schemes in F q 3 and showed that the number of inequivalent such schemes grows exponentially.…”
mentioning
confidence: 99%